Does hereditary angioedema make COVID-19 worse? - Xu, Yingyang (World Allergy Organ J, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has spread rapidly worldwide. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent for COVID-19, enters host cells via angiotensin-converting enzyme 2 (ACE2) and depletes ACE2, which is necessary for bradykinin metabolism. The depletion of ACE2 results in the accumulation of des-Arg (9)-bradykinin and possible bradykinin, both of which bind to bradykinin receptors and induce vasodilation, lung injury, and inflammation. It is well known that an overactivated contact system and excessive production of bradykinin comprise the key mechanisms that drive the pathogenesis of hereditary angioedema (HAE). It is reasonable to speculate that COVID-19 may increase disease activity in patients with HAE and vice versa. In this review, we explore the potential interactions between COVID-19 and HAE in terms of the contact system, the complement system, cytokine release, increased T helper 17 cells, and hematologic abnormalities. We conclude with the hypothesis that comorbidity with HAE might favor COVID-19 progression and may worsen its outcomes, while COVID-19 might in turn aggravate pre-existing HAE and prompt the onset of HAE in asymptomatic carriers of HAE-related mutations. Based on the pathophysiologic links, we suggest that long-term prophylaxis should be considered in patients with HAE at risk of SARS-CoV-2 infection, especially the prophylactic use of C1 inhibitor and lanadelumab and that HAE patients must have medications for acute attacks of angioedema. Additionally, therapeutic strategies employed in HAE should be considered for the treatment of COVID-19, and clinical trials should be performed.